Level and predictors of nurse caring behaviors among nurses serving in inpatient departments in public hospitals in Harari region, eastern Ethiopia - Haregeweyn Kibret; Barkot Tadesse; Adera Debella; Meron Degefa; Lemma Demissie Regassa (BMC, 2022)
Abstract Background Nursing practice is centered on caring and nurses' behaviour has an impact on the quality of patient care and it is predictive of patient satisfaction,however, many nurses, in reality, do not exhibit caring behavior when providing nursing care to clients. This study was aimed to assess the level and predictors of nurse caring behaviors among nurses serving in inpatient departments in public hospitals in Harari Region of Ethiopia from March 10 to April 10, 2021. Method A cross-sectional study was conducted among 300 nurses providing inpatient service in public hospitals in the Harari region of eastern Ethiopia. All permanent nurses working in major inpatient services of two public hospitals, namely Jugal General Hospital (JGH) and Hiwot Fana Specialized University Hospital (HFSUH) were included. The English version of the CNPI-Nurse scale was used to determine the level of caring behavior. The association was reported using the crude and adjusted odds ratios along with the 95% confidence interval. The statistical significance of the association was declared at p-value < 0.05. Result The caring behavior was classified as high and low based on the median score. According to this study only 51.67% (95% CI:45.97, 57.35%) of nurses had good caring behavior. The odds of having good caring behavior were 2.22 (AOR = 2.22, 95%CI: 1.20, 4.10) times higher among nurses working in good working environment compared to those who work in bad working environment. Nurses who were satisfied with their job had 2.79 (AOR: 2.79, 95%CI: 1.54, 5.08) times higher odds of good caring behavior than those who were not satisfied with their job. Similarly, nurses who had a lower workload had a 3.01 (AOR: 3.01, 95%CI: 1.70, 5.33) times higher probability of having good caring behavior from nurses compared to nurses who reported having a high workload. Conclusion The level of nurses caring behavior is not satisfactory and it is influenced by working environment characteristics, job satisfaction and workload. Therefore it necessary to creat conducive working environment, provide adequate time and resources inorder to improve the level of nurses caring behaviour.